Quality of life among caregivers of patients with severe mental illness in northwest Ethiopia, 2022: an institutional-based cross-sectional study - Munie, Birhanu Mengist; Guangul, Melak Menberu; Mamaru, Almaz; Asnakew, Sintayehu; Amha, Haile; Tedla, Assasahegn (Frontiers in Psychiatry, 2024)
Background: Severe mental illness has negative consequences not only for the person suffering from it but also for their caregiver’s quality of life and the community in which they reside. These impacts could be particularly visible in low- and middle- income countries, where the treatment gap for mental illnesses is particularly high. There is a dearth of evidence in Ethiopia. Objective: To assess quality of life and its associated factors among caregivers of patients with severe mental illness at Felege Hiwot and Tibebe Ghion Compressive Specialized Hospital, Bahir Dar, Northwest Ethiopia, 2022. Methods: An institution-based cross-sectional study design was conducted at Felege Hiwot and Tibebe Ghion Compressive Specialized Hospitals from June 13 to July 13, 2022. A systematic random sample technique was utilized to select 469 study participants the World Health Organization quality of life Bref questionnaire was utilized to assess quality of life, and perceived stigma was measured through family interview schedule questionnaire. The data were gathered using the epicollect5 software with a face-to-face interview method and then exported to SPSS-25. Simple and multiple linear regression analyses were conducted to identify associated factors of quality of life of variables that are statistically significant (P-value < 0.05) with B-coefficients and a 95% CI. Descriptive statistics were used to describe the outcome and predictor variables. Results: A total of 456 respondents participated, with a response rate of 97.2%. The result showed that the mean quality of life score of caregivers of patients with severe mental illness for each domain (mean ± standard deviations) was between 46.5 ± 18.7 - 51.2 ± 19.9, with the worst score of zero in the environmental domain and 94 in the social domain. In multiple regression, living in a rural area (B=-5.2, 95% CI;-8.9,-1.8), being illiterate (B=-7.2, 95% CI,-10.6,-3.7), having chronic medical illness (B=-5.2, 95% CI,-8.6, -1.7), having probable cases of anxiety (B=-6.9,95% CI,-10.5,-13.3), having probable cases of depression (B=-4.9,95% CI,-8.2,-1.7), and the presence of perceived stigma (B=-7.9,95% CI,-11.2,-4.77) were significantly associated with the overall quality of life. It predicts above 40% of the variability in each domain.